Effect of coenzyme Q10 concentration on post-freezing ovine semen - Loja Jiménez, Evelyn (2025)
Reproductive biotechnologies have become a fundamental component for increasing productive efficiency. These tools address issues related to infertility and productivity in the species, whose genetic material is highly sensitive to external environmental variations and improper handling. In this context, coenzyme Q10 (Ubiquinone) is a substance that plays an important role in ovine semen cryopreservation, acting as an antioxidant in sperm survival. Therefore, this study evaluated the effect of different concentrations of coenzyme Q10 on post-freezing ovine semen, using various doses (0.2 mM; 0.4 mM; 0.6 mM; and 0.8 mM). For this purpose, samples were collected and frozen from 3 individuals, with 5 repetitions; each sample was divided into 4 doses plus a control. When evaluated fresh, the semen presented promising qualitative characteristics consistent with the literature; however, the results of coenzyme Q10 addition post-freezing showed values contrary to those of fresh semen regarding indicators such as Motility, Membrane Functionality, Viability, and Vitality defined by the CASA system (Computer Assisted Sperm Analysis System), associating this reduction with the presence of coenzyme Q10 in the frozen medium. The Membrane Functionality and Viability tests revealed a reduction in these indicators associated with the concentration of coenzyme Q10. These values provide an essential basis to consider for future research involving additives and antioxidants in ovine semen.